Peningkatan Kualitas Masyarakat Melalui Penerapan “Say CHSE” Dan Pembuatan Masker Tie Dye Di Era Covid-19, Kampung Situ Bolang - Vyana Lohjiwa; Riadi Darwis; Endah Trihayuningtyas; Tatang Sophian; Renalmon Hutahaean (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2022)
Kampung Wisata Situ Bolang is a community-based tourism area. In the past, Situ Bolang was a natural lake that became a tourist destination for community. Unfortunately, due to the impact of the toll road construction, the springs are blocked so there is no supply of lake water; the lake is converted into rice fields; now the community has lost their source of clean water; The occurrence of land conversion for housing, road access, and industry has changed the habit pattern of the farming community into unskilled labour. Behind the irony, it turns out that there is an opportunity that can be developed which is currently guarded by the community, namely Martial Arts of Nampon style. Nampon martial arts being so special because the first students are Ir. Soekarno (the first President of the Republic of Indonesia) and Moch. Natsir. In addition to martial arts, there are several people who like to paint, even the paintings have been marketed to the ASEAN region. As an effort to preserve community-based culture in the era of the COVID-19 Pandemic, it is necessary to increase community capacity through training in the application of the Cleanliness, Health, and Environmental Sustainability (CHSE) concept in the Situ Bolang Tourism Area, otherwise to push the potential of people who like to paint, it can be utilized in making painted masks/tie dye motifs as an alternative souvenirs from Situ Bolang. Keywords: Community Enhancement; Situ Bolang; Nampon Martial Arts; CHSE; Tie Dye Masks